The effect of low-level laser therapy on rat unicortical femoral defect - Çomakli, Selim; Ersöz, Uğur; Turgut, Ferda; Yanmaz, Latif Emrah; Okur, Sıtkıcan; Okumus, Zafer; Yildirim, Betül; Sağlam, Yavuz Selim; Karataş, Özhan; Dogan, Elif (Office of Academic Resources, Chulalongkorn University - DIGITAL COMMONS JOURNALS, 2021)
The Thai Journal of Veterinary Medicine, 51, 2, 277
Keywords: Healing; Rat; Defect; Femur; Bone; 3. Good health